EARLY PROTECTION OF CARIES EVENTS IN STUDENTS OF ELEMENTARY SCHOOL LESANPURO 2, KEDUNGKANDANG DISTRICT, MALANG CITY - Widodorini, Trining; Sutanti, Viranda; Hernani M, Yully Endang (Caring: Jurnal Pengabdian Masyarakat, 2023)
Efforts to maintain dental and oral health should be done as early as possible so that dental caries can be prevented so as not to cause infection problems in children in the future. A tooth infection requires medical treatment because the infection can spread to other parts of the body such as the jaw, neck or head and cause other health problems. Parents and schools are one of the closest environments for children to train a child's motor skills, including brushing their teeth. The ability to brush teeth properly and early protective measures are quite important factors for maintaining teeth and mouth. The purpose of this activity is to reduce the prevalence of caries in elementary school students as early protection against the incidence of dental caries as source of infection in students of Elementary School Lesanpuro 2 Malang City. The design of this activity uses analytic observational with a cross-sectional approach. The sample used was grade 1 and 2 students at Elementary School Lesanpuro 2 with a total of 60 students. From the results of measuring knowledge, it was found that the average increase before and after being given education was from 86.92 to 97.75 and statistically there was a significant difference (p=0.000). Early protection interventions with dental and oral health education, brushing teeth together and topical application of fluoride can increase knowledge about caries and its prevention because there is an increase in knowledge about caries prevention after the intervention was carried out on students at Elementary School Lesanpuro 2.